RELIGIOSITY AND INTENTION TO ADOPT ISLAMIC FINANCING: INDIVIDUAL CONTROL AS A MEDIATOR? - Isnaini, Araina; Risna Wijayanti; Sumiati (CV. Radja Publika, 2023)
Islamic Financing in Indonesia has not fully received the public's attention because the application of Islamic financing does not follow Sharia principles and Islamic law. This literature review aims to assist in understanding Islamic financing concerning the intention to use Islamic financing from the perspective of MSME owner-managers. Literature review method based on journals related to the keywords